2019
DOI: 10.1111/cea.13407
|View full text |Cite
|
Sign up to set email alerts
|

Perceived triggers of asthma impair quality of life in children with asthma

Abstract: BackgroundData on the impact of the number and nature of perceived asthma triggers on health‐related quality of life (HRQL) in children are scarce.ObjectiveTo investigate the impact of perceived asthma triggers on both asthma‐specific and generic HRQL in children.MethodsA cross‐sectional study was conducted among children (7‐18 years) with asthma in secondary and tertiary care. Children were screened with electronic questionnaires regarding respiratory and allergic symptoms. Asthma‐specific HRQL was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
(44 reference statements)
0
12
0
1
Order By: Relevance
“…Physical exercise is important to maintaining a high quality of life ( Kansen et al, 2019 ). Dantas et al (2014) evaluating the maternal perception of physical activity in adolescents with asthma, showed that 96% of mothers thought that physical activity was important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical exercise is important to maintaining a high quality of life ( Kansen et al, 2019 ). Dantas et al (2014) evaluating the maternal perception of physical activity in adolescents with asthma, showed that 96% of mothers thought that physical activity was important.…”
Section: Discussionmentioning
confidence: 99%
“…Of the mothers evaluated, 37% said that they imposed restrictions on their children’s physical activities (sports/games) even during periods when the children were not suffering from asthma exacerbations. In individuals with asthma, FEV 1 , before or after bronchodilator use, does not correlate with VO 2 peak , the anaerobic threshold, or peripheral oxygen saturation ( Kansen et al, 2019 ). The respiratory system, at least in individuals with mild asthma, is able to respond adequately to the demands for increased airflow during high-intensity aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, on a slightly different note, Kansen and colleagues have looked at asthma triggers amongst children referred for secondary care the number of allergic and non-allergic asthma triggers were strongly associated with quality of life. 77 The study emphasises the importance of considering triggers and providing amelioration where possible. It also underlines the importance of knowing the atopic status of children and the importance of possible atopic triggers.…”
Section: Asthma In Disadvantaged Populations and Comorbiditiesmentioning
confidence: 99%
“…Kansen et al have looked at the impact of triggers on quality of life in childhood asthma . A total of 527 children aged 7 to 18 years were included, they were treated in secondary or tertiary care.…”
mentioning
confidence: 99%